George Kennan’s Photography Collection of Political Exiles in Labor Camps of Late Imperial Siberia - Garth, Maria (Journal of Russian American Studies, 2022)
This article examines an album of photographs compiled by the American explorer and scholar George Kennan (1845-1924) on the topic of political exiles in Imperial Russia. As a result of his travels through Russia, Kennan began a large collection of photographs of political prisoners and later donated this album to the New York Public Library shortly before his death. The people in these portraits, some of whom Kennan knew personally, were sentenced to exile and forced labor in Siberia in the late nineteenth century as a result of their anti-tsarist political views. During the extended process of constructing the album from photographs and texts in his archive, Kennan created a multimedia examination of the exile experience which destabilizes traditional narratives of Imperial histories. As a recognized expert on Russia, Kennan built a reputation on his knowledge of Russian politics and personal relationships with revolutionary figures. Through a close analysis of Kennan’s methods and motivations, this article argues that the album of photographs shows Kennan’s deep engagement with politics, memory, and history in the field of Russian-American studies.